2015
DOI: 10.3923/std.2015.215.220
|View full text |Cite
|
Sign up to set email alerts
|

An Insight into Phytoremediation of Heavy Metals from Soil Assisted by Ancient Fungi from Glomeromycota-Arbuscular Mycorrhizal Fungi

Abstract: Arbuscular Mycorrhizal (AM) fungi form mutualistic relationship with plant roots which improves plant growth and confers tolerance against many types of stresses, including heavy metals tolerance. AM fungi allows enhanced-growth of plants, grown on heavy metals contaminated soil. They have been involved in regulating the uptake of heavy metals from root to shoot exploiting the potential of membrane transporters. These fungi either increase the uptake of heavy metals from root to shoot (phytoextraction) or stop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…having more than one cell wall, so it has a stronger defense against heavy metal stress than Gigaspora sp. According to Upadhyaya et al (2010) and Koohi (2014) that endomycorrhizae can store heavy metals in hyphal cell walls, specifically stored in crystalloids in the mycelium, this explanation reinforced by Chaves et al (2002) and who show that in roots of plants that are contaminated with heavy metals, it is seen that the endomycorrhizal extra radical mycelium is able to absorb and accumulate heavy metals outside the mushyel wall of hyphal wall zone, in cell wall, and in cytoplasm of fungus hyphae, while the research results of Tuheteru et al (2017) show that utilization Acaulospora tuberculata can increase Mn, Fe, Cr and Ni uptake of Nauclea orientalis L. Several studies have reported that indigenous endomycorrhiza effectively and efficiently infect endodermis of plant roots in areas that are contaminated with heavy metals (Vaishaly et al, 2015;Shakeel and Yaseen, 2015;Kumar and Saxena, 2019). According to Zadehbagheri et al (2014) that indigenous endomycorrhizal isolates that develop and reproduce naturally in areas contaminated with heavy metals are more tolerant than isolates originating from non-polluted areas.…”
Section: Resultsmentioning
confidence: 99%
“…having more than one cell wall, so it has a stronger defense against heavy metal stress than Gigaspora sp. According to Upadhyaya et al (2010) and Koohi (2014) that endomycorrhizae can store heavy metals in hyphal cell walls, specifically stored in crystalloids in the mycelium, this explanation reinforced by Chaves et al (2002) and who show that in roots of plants that are contaminated with heavy metals, it is seen that the endomycorrhizal extra radical mycelium is able to absorb and accumulate heavy metals outside the mushyel wall of hyphal wall zone, in cell wall, and in cytoplasm of fungus hyphae, while the research results of Tuheteru et al (2017) show that utilization Acaulospora tuberculata can increase Mn, Fe, Cr and Ni uptake of Nauclea orientalis L. Several studies have reported that indigenous endomycorrhiza effectively and efficiently infect endodermis of plant roots in areas that are contaminated with heavy metals (Vaishaly et al, 2015;Shakeel and Yaseen, 2015;Kumar and Saxena, 2019). According to Zadehbagheri et al (2014) that indigenous endomycorrhizal isolates that develop and reproduce naturally in areas contaminated with heavy metals are more tolerant than isolates originating from non-polluted areas.…”
Section: Resultsmentioning
confidence: 99%